Intestinal Mucosal Triacylglycerol Accumulation Secondary to Decreased Lipid Secretion in Obese and High Fat Fed Mice - Douglass, John D.; Malik, Nashmia; Chon, Su-Hyoun; Wells, Kevin; Zhou, Yin Xiu; Choi, Andrew S.; Joseph, Laurie B.; Storch, Judith (Frontiers in Physiology, 2012)
The ectopic deposition of fat in liver and muscle during obesity is well established, however surprisingly little is known about the intestine. We used the ob/ob mouse and C57BL6/J mice fed a high fat (HF) diet to examine the effects of obesity and the effects of HF feeding, respectively, on intestinal mucosal triacylglycerol (TG) accumulation. Male C57BL6/J (WT) mice were fed low fat (LF; 10% kcal as fat) or HF (45%) diets, and ob/ob mice were fed the LF diet, for 3 weeks. In this time frame, the WT-HF mice did not become obese, enabling independent examination of effects of the HF diet and effects of obesity. Analysis of intestinal lipid extracts from fed and fasted animals demonstrated that the mucosa, like other tissues, accumulates excess lipid. In the fed state, mucosal triacylglycerol (TG) levels were 3-fold and 5-fold higher in the WT-HF and ob/ob mice, respectively, relative to the WT-LF mice. In the fasted state, mucosa from ob/ob mice had 3-fold higher TG levels relative to WT-LF mucosa. q-PCR analysis of mucosal mRNA from fed-state mice showed alterations in the expression of several genes related to both anabolic and catabolic lipid metabolism pathways in WT-HF and ob/ob mice relative to WT-LF controls. Fewer changes were found in mucosal samples from the fasted-state animals. Remarkably, oral fat tolerance tests showed a striking reduction in the plasma appearance of an oral fat load in the ob/ob and WT-HF mice compared to WT-LF. Overall, the results demonstrate that the intestinal mucosa accumulates excess TG during obesity. Changes in the expression of lipid metabolic and transport genes, as well as reduced secretion of dietary lipid from the mucosal cells into the circulation, may contribute to the TG accumulation in intestinal mucosa during obesity. Moreover, even in the absence of frank obesity, HF feeding leads to a large decrease in the rate of intestinal lipid secretion.